Exploring anger as a moderator of narcissism and antisocial behaviour on tinder. (15th July 2020) - March, Evita; Grieve, Rachel; Wagstaff, Danielle; Slocum, Alexandra
Highlights: Inconsistent relationship between narcissism and antisocial behaviour on Tinder. Explored anger as a moderator of narcissism and antisocial behaviour on Tinder. Anger significantly moderated relationship between narcissism and harassment. Anger significantly moderated relationship between narcissism and aggression. Anger experienced as a response to ego-threat may best predict hostile behaviour. Abstract: In an attempt to address inconsistency in the literature regarding narcissism and online antisocial behaviour, we applied the theory of threatened egotism and aggression to examine whether anger moderates the relationship between narcissism and antisocial behaviour on Tinder. Specifically, we explored anger moderating the relationship between narcissistic subtypes of Grandiose Exhibitionism and Entitlement Exploitative and perpetration of antisocial behaviour (aggression and harassment) on Tinder. Tinder users ( N  = 1, 001; 46.3% men and 53.7% women) with an average age of 22.42 years ( SD  = 4.31) completed an anonymous online questionnaire. Anger was a significant moderator of all relationships between narcissism and antisocial behaviour. Specifically, at average and high levels of anger there were positive, significant relationships between both facets of narcissism, and aggression and harassment on Tinder. These results indicate that trait narcissism alone may not explain perpetration of antisocial behaviour on Tinder, and to adequately explore this relationship future research should consider the role of threatened egotism.